PENDAMPINGAN PIDATO BAHASA INGGRIS BAGI ANGGOTA IPPNU RANTING SIMBANG KULON - Inayatul Ulya (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2023)
Teenage years is time to begin preparing teenagers future life, they need foundation for being organized person. That was why joining organization was one of good ways. One of the organization which is provided for teenage female, is IPPNU. By joining an organization, they can manage their time, their leadership will be developed and they would be cooperative. Annually, there are some event which are hold to give the opportunity for the members to perform their ability, one of them is PORSENI. However, when joining this event, they have less confidence. That is why, an accompaniment needs to be held, especially on performing English Speech. This agenda was held in three stages, they are modelling, practice, and feedback. The lecturer gave example on how to write English speech and perform it. Then, the participants practiced writing the speech and performed it. Finally, the lecturer gave feedback on their performance. The result of this agenda showed that the participants were enthusiastic for doing the practice, they got improvement. It was proved when they joined the English Speech Competition in PORSENI, one of them became the 2nd runner up.